Grammar-based model transformations: Definition, execution, and quality properties. (October 2015) - Besova, Galina; Steenken, Dominik; Wehrheim, Heike
Abstract: Model transformation is a key concept in model-driven software engineering. The definition of model transformations is usually based on meta-models describing the abstract syntax of languages. While meta-models are thereby able to abstract from superfluous details of concrete syntax, they often loose structural information inherent in languages, like information on model elements always occurring together in particular shapes. As a consequence, model transformations cannot naturally re-use language structures, thus leading to unnecessary complexity in their development as well as in quality assurance. In this paper, we propose a new approach to model transformation development which allows to simplify the developed transformations and improve their quality via the exploitation of the languages׳ structures. The approach is based on context-free graph grammars and transformations defined by pairing productions of source and target grammars. We show that such transformations have important properties: they terminate and are sound, complete, and deterministic . Abstract : Highlights: Approach uses grammar-based definition of languages to create quality transformations. It simplifies transformation development using structural mappings between languages. We define sufficient conditions on grammar-based transformations for their quality. Such transformations are by-construction terminating, sound, complete and deterministic.